Association between Dietary Potassium Intake and Nonalcoholic Fatty Liver Disease and Advanced Hepatic Fibrosis in U.S. Adults - Hao-Kai Chen; Qi-Wen Lan; Yu-Jia Li; Qing Xin; Run-Qi Luo; Jun-Jie Wang (International Journal of Endocrinology, 2024)
Introduction. The correlation between potassium and nonalcoholic fatty liver disease (NAFLD) is currently still poorly understood. We conducted this study to explore the correlation between dietary potassium intake and NAFLD, as well as advanced hepatic fibrosis (AHF). The study also sought to identify any potential interactions. Methods. The data employed in this study were obtained from the National Health and Nutrition Examination Survey (NHANES) program, encompassing a period from 2007 to 2018. Employing the multiple logistic regression analysis, we evaluated the association of dietary potassium intake with NAFLD and AHF. Subsequently, stratification analysis, based on demographic variables, was constructed so as to assess the stability of the results. In addition, potential interaction effects were assessed by interaction tests. Results. A total of 9443 participants were included in the analysis. The mean age of the participants was 50.4 years, and their daily mean dietary potassium and vitamin C intake was 2556.49 mg and 82.93 mg, respectively. Following comprehensive statistical analyses, the findings indicated a negative correlation between dietary potassium intake and both NAFLD and AHF. Participants in Q4 group with dietary potassium intake exhibited a 31% and 42% reduction in the odds of developing NAFLD and AHF, respectively, in comparison to Q1 group. An interaction effect of dietary vitamin C intake was observed in the association between dietary potassium intake and NAFLD. The results imply that high dietary vitamin C intake augment the inverse relationship between dietary potassium intake and NAFLD. Conclusion. Dietary potassium intake was found to have an inverse association with the odds of both NAFLD and AHF. The association between dietary potassium intake and NAFLD was amplified by the presence of vitamin C in the diet.